Penguatan Keimanan Umat di Kecamatan Manggala Melalui Program KKN STIBA Makassar - Ahmad Syaripudin; Zulfiah Sam (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
Manggala Subdistrict is one of 14 subdistricts in Makassar City. The area of Manggala sub-district is 24.14 km2 or 13.73% of the area of Makassar City. Manggala sub-district consists of 8 villages namely Bontoala, Bangkala, Batua, Borong, Manggala, Tamangapa, Biring Romang and Antang. The purpose of this STIBA Makassar Real Work Lecture (KKN) batch IV is a form of community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing community service programs begins with mapping the problems and needs of the community using SOAR. After the analysis is carried out, a work program that is appropriate and needed by the community is prepared. Work programs that have been successfully implemented include: Socialization and Gathering, Clean Saturdays in Manggala District, Makassar City, Book Review